In vivo Evaluation of Patellar Tendon Stiffness in Individuals with Patellofemoral Pain Syndrome - Hsin-Yi Liu; Michelle Boling; Darin Padua; R. Alexander Creighton; Paul Weinhold (Applied Bionics and Biomechanics)
The objective of this study was to utilise an ultrasonic technique to assess the effect of patellofemoral pain syndrome (PFPS) on the mechanical properties of the patellar tendon. Seven subjects with PFPS and seven matched control subjects volunteered to participate in this study. Subjects were asked to perform isometric maximal voluntary contractions of the knee extensors while their knee extension torque was monitored and the displacement of the patellar tendon was recorded with an ultrasonic system. Our results showed significantly lower tendon stiffness (by ∼30%) in the PFPS subjects. Although tendon secant modulus was lower by 34% in the PFPS subjects, the difference was not statistically significant. Therefore, we conclude that the ultrasonic technique was able to detect a decrease in the structural stiffness of the patellar tendon associated with PFPS. The decrease in tendon stiffness was moderately correlated with the length of symptoms in these individuals.